Inferno: between the times - фон Бальтазар, Ханс Урс (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2017)
This article studies the image of God in the first canticle of “The Divine Comedy”. The author proceeds from the assertion that the poem lacks the image   of   the   suffering   Christ   and   claims   that   this   absence   displaces   the Christological   and Trinitarian   ideas   from   the   theological   framework   of   the text. The analysis of the poetic image of Hell determines that in its description Dante was guided by the image of ancient Hades, rather than by the theological representations. The author demonstrates how the mixing of ancient and Christian worldview displaces the figure of Christ from the center of Universe and replaces it with an all-encompassing Eros.